Shape Matters: Crystal Morphology and Surface Topography Alter Bioactivity of Bioceramics in Simulated Body Fluid. Issue 9 (28th May 2020) - Myszka, Barbara; Schodder, Philipp I.; Leupold, Simon; Barr, Maïssa K. S.; Hurle, Katrin; Schüßler, Martina; Demmert, Benedikt; Biggemann, Jonas; Fey, Tobias; Boccaccini, Aldo R.; Wolf, Stephan E.
Abstract : For bioactive biomaterials such as bioceramics and bioglass, it is generally accepted that, apart from acting as heterogeneous nucleators, it is their solubility and the resulting release of relevant ions such as calcium or basic anions which mainly governs the biomaterial's bioactivity. This contribution reveals that this bioactivity, as assessed by simulated body fluid (SBF), can also be considerably modified by the bioceramic's morphology, i.e., bioactivity is also governed by microstructure and surface morphology. When crystals are forced to adopt out‐of‐equilibrium crystal habit, this simple change in morphology converts an essentially bioinert material, here calcite, into a bioceramic which shows bioactivity in SBF. On larger length scales, already simple morphological changes, such as scratches, can have inverse effects. Limited mass transport into grooves and pits on a bioceramic surface can lead to local ion depletion which, in turn, causes reduced bioactivity of bioceramics which, otherwise, show distinct bioactivity in SBF. This contribution emblematically illustrates the unforeseen importance of even minor morphology changes on different length scales when assessing and designing a biomaterial's bioactivity through SBF assays. Abstract : It is often assumed that a bioceramic's solubility and heterogenous nucleation capabilities mainly govern its bioactivity. However, morphological alterations can strongly impact on local ion concentrations and thus fundamentally alter bioactivity. Changes in crystal morphology, thus microstructure, convert a bioinert into a bioactive bioceramic. Contrastingly, simple topography changes, e.g., scratches, locally impede bioactivity of otherwise bioactive materials.